Tomato Yellow Leaf Curl Virus V2 Protein Plays a Critical Role in the Nuclear Export of V1 Protein and Viral Systemic Infection - Zhao, Wenhao; Wu, Shuhua; Barton, Elizabeth; Fan, Yongjian; Ji, Yinghua; Wang, Xiaofeng; Zhou, Yijun (Frontiers in Microbiology, 2020)
Geminiviruses are an important group of circular, single-stranded DNA viruses that cause devastating diseases in crops. Geminiviruses replicate their genomic DNA in the nucleus and the newly-synthesized viral DNA is subsequently transported to the cytoplasm for further cell-to-cell and long-distance movement to establish systemic infection. Thus, nucleocytoplasmic transportation is crucial for successful infection by geminiviruses. For Tomato yellow leaf curl virus (TYLCV), the V1 protein is known to bind and shuttle viral genomic DNA, however, the role of the V2 protein in this process is still unclear. Here, we report that the V1 protein is primarily localized in the nucleus when expressed but the nucleus-localized V1 protein dramatically decreases when co-expressed with V2 protein. Moreover, the V2-facilitated nuclear export of V1 protein depends on host exportin-⍺ and a specific V1-V2 interaction. Chemical inhibition of exportin-⍺ or a substitution at cysteine 85 of the V2 protein, which abolishes the V1-V2 interaction, blocks redistribution of the V1 protein to the perinuclear region and the cytoplasm. When the V2C85S mutation is incorporated into a TYLCV infectious clone, the TYLCV-C85S causes delayed onset of very mild symptoms compared to wild-type TYLCV, suggesting that the V1-V2 interaction and, thus, the V2-mediated nuclear export of the V1 protein is crucial for viral spread and systemic infection. Our data point to a critical role of the V2 protein in promoting the nuclear export of the V1 protein and viral systemic infection, likely by promoting V1 protein-mediated nucleocytoplasmic transportation of TYLCV genomic DNA.